2020
DOI: 10.5194/soil-2020-69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continental-scale controls on soil organic carbon across sub-Saharan Africa

Abstract: Abstract. Earlier studies have demonstrated that soil texture and geochemistry strongly affect soil organic carbon (SOC) content. However, those findings primarily rely on data from temperate regions with soil mineralogy, weathering status and climatic conditions that generally differ from tropical and sub-tropical regions. We investigated soil properties and climate variables influencing SOC concentrations across sub-Saharan Africa. A total of 1,601 samples were analyzed, collected from two depths (0–20 cm an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…5). This result is in line with findings from a continental-scale study across sub-Saharan Africa where climate and geochemistry are more important predictors of SOC content than aboveground carbon inputs (von Fromm et al, 2020). The importance of NPP may largely depend on how much NPP ends up in the soil and how it is translocated to different depths (Wang et al, 2021).…”
Section: Secondary Role Of Carbon Inputs In Determining Spatial Variasupporting
confidence: 88%
See 1 more Smart Citation
“…5). This result is in line with findings from a continental-scale study across sub-Saharan Africa where climate and geochemistry are more important predictors of SOC content than aboveground carbon inputs (von Fromm et al, 2020). The importance of NPP may largely depend on how much NPP ends up in the soil and how it is translocated to different depths (Wang et al, 2021).…”
Section: Secondary Role Of Carbon Inputs In Determining Spatial Variasupporting
confidence: 88%
“…More importantly, soil carbon can be physically protected from decomposition via occlusion with soil aggregates and binding with minerals (Lehmann and Kleber, 2015;Dungait et al, 2012;Schmidt et al, 2011), while the protection capacity is largely determined by soil physicochemical properties (Six et al, 2000). These physical protection processes may lead to soil-dependent stabilization/destabilization of different soil carbon substrates (Waldrop and Firestone, 2004;Keiluweit et al, 2015;Six et al, 2002). However, it should be noted that complex interplays of various soil properties are involved in SOC stabilization and destabilization processes.…”
Section: The Importance Of Soil Propertiesmentioning
confidence: 99%
“…Local studies have shown that PCMs are correlated with SOC stocks across soils of different ages, climates, and parent materials (Dahlgren et al 1997;Torn et al 1997;Chadwick et al 2003;Masiello et al 2004;Heckman et al 2009;Rasmussen et al 2018b). More expansive, continental scale data syntheses indicate that PCMs play a major role in SOC storage in humid climates (Rasmussen et al 2018a;Kramer and Chadwick 2018;von Fromm et al 2020). These studies relate PCMs to SOC; however, they have not specifically evaluated the role of primary mineral weathering in controlling PCM abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, von Fromm et al. (2020) pointed to the ratio of the annual PET to the MAP as the best predictor for SOC distribution. The mean age of SOC also relates to global climate ( Shi et al., 2020).…”
Section: The Old Tool and The New Challengementioning
confidence: 92%
“…These relations decisively increase our understanding of general patterns contributing to stabilizing C in the soil at scales relevant for C management. By definition, the HLZ classification cannot go beyond climate control, but the latest literature ( Kramer and Chadwick , 2018; Rasmussen et al., 2018; Hein et al., 2020; von Fromm et al., 2020) indicates that multiple controls on SOC persistence vary systematically with climate. HLZ is a good fit to separate SOC stocks into clearly distinguishable and process‐oriented zones, varying in their mechanisms to mediate SOC persistence.…”
Section: Beyond Climate Control Of Soc Stocksmentioning
confidence: 99%